Book Review: Indu Prakash Singh, CityMakers: Tribulations and Triumphs – A Saga of Heroic Struggle of the Homeless Residents of India. Issue 1 (April 2017) - Mehta, Simi; Kumar, Arjun
Indu Prakash Singh, CityMakers: Tribulations and Triumphs – A Saga of Heroic Struggle of the Homeless Residents of India . New Delhi: Mukul Prakashan, 2016, ₹1000, 608 pp.